African Theology in the 21st Century: Mapping Out Critical Priorities - Waweru, Humphrey Mwangi (European Scientific Journal, ESJ, 2018)
There is a dialogue taking place in the area of African Theology; â€œdo we call it African Christian theology or African Theology and how it relates to the African cultureâ€? Depending on where one sits, any name will carry the day as long as it fulfills the academic desire intended. What is important is the dialogue that is taking place between the Bible and the African culture. Here, we shall take the name â€œAfrican Theologyâ€ as the norm. It is evident in almost all ways that from a walk which is based on the mapping of African theology or from the wide variety of current understandings of its nature and task, there are several priorities in African Theology. A number of theologians today argue that the priorities of African theology are many. These include providing a clear and comprehensive dialogue between African culture and the Bible in relation to the African faith. They argue that the Bible has also been translated into local languages in order to enable the African cultures to become intelligible in the way they relate to the scriptures. On the other hand, others have prioritized the definition of African Theology so that they can deal with it from their perspective of African Traditional Religions. Also, others want to prioritize African Theology as a reflection of the praxis of Christian faith within a relatively deprived community. Therefore, this article seeks to briefly provide some priorities in African Theology, such as liberation, reconstruction, and poverty reduction theologies. In this study, we will proceed to explore the need for a definition of African Theology, how it relates to African Christian faith, and the challenges posed by African Theology to the Christian faith. We will conclude with the general guidelines on formulating the priorities of African theology.